On a linearization technique for solving the quadratic set covering problem and variations - Pandey, Pooja; Punnen, Abraham P. (Optimization letters, 2017)
In this paper we identify various inaccuracies in the paper by Saxena and Arora (Optimization 39:33–42, 1997 ). In particular, we observe that their algorithm does not guarantee optimality, contrary to what is claimed. Experimental analysis has been carried out to assess the value of this algorithm as a heuristic. The results disclose that for some classes of problems the Saxena–Arora algorithm is effective in achieving good quality solutions while for some other classes of problems, its performance is poor. We also discuss similar inaccuracies in another related paper.